Mechanisms of resistance and their interactions in twelve sources of resistance to biotype E greenbug (Homoptera: Aphididae) in sorghum - Dixon, O.A.G.; Bramel-Cox, P.J.; Reese, J.C.; Harvey, T.L. (Oxford University Press, 1990)
Evaluation of mechanisms of resistance among 12 grain sorghum, Sorghum bicolor (L.) Moench, sources of resistance to the biotype E greenbug, Sehizaphis graminum (Rondani), indicated that the most important mechanism within this germplasm seemed to be antibiosis (with a few exceptions). The source with the highest level of overall resistance was PI266965, which had also the highest level of antibiosis. The highest level of tolerance was found in PI229828, and the highest level of antixenosis was found in ‘J242.’ All mechanisms of resistance in the various plant stages were independent, and only antibiosis in the seedling stages was highly related to average damage score from the usual flat screening technique. Principal component analysis was used to develop an index to maximize variation among accessions, describe each germplasm’s overall resistance, and compare the known sources of resistance with any susceptible sources or any new sources of resistance in relation to host plant interactions.